2016
DOI: 10.1186/s13048-016-0271-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylated APC in serous carcinoma based on a meta-analysis of ovarian cancer

Abstract: BackgroundThe reduced expression of the Adenomatous polyposis coli (APC) gene, a tumor suppressor gene, through promoter hypermethylation has been reported to play a key role in the carcinogenesis. However, the correlation between APC promoter hypermethylation and ovarian cancer (OC) remains to be clarified.MethodsA comprehensive literature search was carried out in related research databases. The overall odds ratio (OR) and corresponding 95 % confidence interval (CI) were used to evaluate the effects of APC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…Decreases in the expression of certain components of the destruction complex are frequently observed in EOC [61]. For example, several studies have reported significantly higher methylation rates in the promoter region of APC in EOC tumors when compared to benign ovarian tumors or normal ovarian tissue samples [6264]. However, the mechanisms underlying the hypermethylation and suppression of APC in EOC are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in the expression of certain components of the destruction complex are frequently observed in EOC [61]. For example, several studies have reported significantly higher methylation rates in the promoter region of APC in EOC tumors when compared to benign ovarian tumors or normal ovarian tissue samples [6264]. However, the mechanisms underlying the hypermethylation and suppression of APC in EOC are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the correlation of RASSF1A promoter methylation between ovarian cancer and LMP tumors remains to be evaluated. No correlation of methylated CDH1 and APC within the promoter between ovarian carcinoma and LMP tumors was reported by some studies [53, 54]. In our meta-analysis, one study reported that RASSF1A promoter methylation had higher frequency in ovarian cancer (23 patients) compared with LMP tumors (23 patients) [40].…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has proven that ovarian cancer is a genetic disease, which depends on alteration of multi‐cancer genes and anti‐cancer genes, multi‐stages and multi‐pathways, involving a variety of oncogenes activation and anti‐oncogene inactivation . At the present, it is revealed that many genes and their protein products related to ovarian cancer have been explored . For example, APC promoter hypermethylation has been proved highly relevant to the occurrence of ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%